The leading rogue state : the U.S. and human rights - Blau, Judith; Brunsma, David L.; Moncada, Alberto; Zimmer, Catherine ([S.l.] : Paradigm Publishers, 2009)
Most Americans would be surprised to learn that their government has declined to join most other nations in UN treaties addressing inadequate housing, poverty, children's rights, health care, racial discrimination, and migrant workers. Yet this book documents how the U.S. has, for decades, declined to ratify widely accepted treaties on these and many other basic human rights. Providing the first comprehensive topical survey, the contributors build a case and specific agendas for the nation to change course and join the world community as a protector of human rights. With Contributions by and on
Keywords: Human rights; International relations; United States